2020
DOI: 10.31557/apjcp.2020.21.9.2751
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Bioinformatics Analysis Reveals Potential Target Genes and TNFα Signaling Inhibition by Brazilin in Metastatic Breast Cancer Cells

Abstract: which leads to relapse and metastasis (Rivera and Gomez, 2010). Developing a strategy that can overcome the progression and metastasis of breast cancer cells is necessary, including the development of new drugs from natural products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 97 publications
1
9
0
Order By: Relevance
“…These findings were in agreement with similar studies, so that cancer-related terms such as collagen fibril organization, extracellular matrix organization [ 65 ], cellular response to amino acid stimulus, platelet activation [ 66 ], tissue homeostasis [ 67 ], regulation of immune response, skin development [ 68 ], platelet-derived growth factor binding, extracellular matrix structural constituent, SMAD binding [ 66 ], extracellular matrix [ 65 ], collagen trimmer, and endoplasmic reticulum lumen [ 66 ] were enriched for 21 selected genes by the RF method. Moreover KEGG pathway enrichment analysis indicated that cancer related pathways such as protein digestion and absorption, platelet activation [ 65 ], focal adhesion, Amoebiasis [ 66 ], human papillomavirus infection [ 69 ], AGE-RAGE signaling pathway in diabetic complications [ 70 ], and relaxin signaling pathway [ 71 ] were significantly enriched which was in agreement with the results of other studies.…”
Section: Discussionsupporting
confidence: 87%
“…These findings were in agreement with similar studies, so that cancer-related terms such as collagen fibril organization, extracellular matrix organization [ 65 ], cellular response to amino acid stimulus, platelet activation [ 66 ], tissue homeostasis [ 67 ], regulation of immune response, skin development [ 68 ], platelet-derived growth factor binding, extracellular matrix structural constituent, SMAD binding [ 66 ], extracellular matrix [ 65 ], collagen trimmer, and endoplasmic reticulum lumen [ 66 ] were enriched for 21 selected genes by the RF method. Moreover KEGG pathway enrichment analysis indicated that cancer related pathways such as protein digestion and absorption, platelet activation [ 65 ], focal adhesion, Amoebiasis [ 66 ], human papillomavirus infection [ 69 ], AGE-RAGE signaling pathway in diabetic complications [ 70 ], and relaxin signaling pathway [ 71 ] were significantly enriched which was in agreement with the results of other studies.…”
Section: Discussionsupporting
confidence: 87%
“…The two most widely studied proteins in the ERBB family: ERBB1 (HER1 or EGFR) and ERBB2 (HER2), was profoundly known to lead to the progression of cancer, which is also crucial to initiate metastasis, as was notable in breast cancer (Hsu and Hung 2016). An other study by Hermawan and Putri (2020) explored the target of brazilin (one of the major compounds in C. sap pan L.) in the TNBC metastatic breast cancer model re vealed that the inhibition of brazilin was possible through blocking in the TNFα pathway. Different features partly influence this distinct mechanism from TNBC with any other subtypes (including ER+ and HER2+).…”
Section: Discussionmentioning
confidence: 99%
“…The microarray data of the two GSE codes were further analyzed using the GEO2R to identify differentially expressed genes (DEGs) (Zhang et al, 2020). The adjusted p-value < 0.05 and Iog fold change > 1 were used to select the significant (Hermawan and Putri, 2020a). The two samples derived from the GSE code were then analyzed using Venny 2.1.0 to obtain a Venn diagram (Liu et al, 2019).…”
Section: Data Miningmentioning
confidence: 99%